FAKTOR-FAKTOR YANG MEMPENGARUHI KESIAPAN MAHASISWA JURUSAN AKUNTANSI DI KOTA MEDAN DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN (MEA) - lili sari anggraini; khairunnisa harahap (Universitas Negeri Medan (UNIMED), 2018)
This study aims to see the influence of ethical competence, knowledge competence, competence ability, relationship competence, and analysis competence to readiness of accounting students in Medan for ASEAN Economic Community (AEC).The population in this study are accounting students from university in Medan. The sampling use purposive sampling method. Questionnaires distributed numbered 410 but returned only 398 and could in though 366. Data analysis use the data quality test, classical assumption, multiple regression analysis and hypothesis testing assisted with SPSS 21.Conclusion of the research is that ethics competence, competence capability, relationship competence, and analysis competence have been well prepared to equip students in facing MEA while knowledge competence’s students is not ready yet and not meet IES standards in facing MEA due to lack of motivation of students and Lack of socialization so that the still low awareness of students to improve competence.